Late Cenozoic tectonic evolution of the Ailao Shan‐Red River fault (SE Tibet): Implications for kinematic change during plateau growth. Issue 8 (30th August 2016) - Wang, Yang; Zhang, Bo; Schoenbohm, Lindsay M.; Zhang, Jinjiang; Zhou, Renjie; Hou, Jianjun; Ai, Sheng
Abstract: Surface uplift, river incision, shear zone exhumation, and displacement along active faults have all interacted to shape the modern landscape in the southeastern margin of the Tibetan Plateau. The Ailao Shan‐Red River fault, a major structure in the tectonic evolution of southeastern Asia, is an excellent recorder of these processes. We present new stratigraphic, structural, and low‐temperature thermochronologic data to explore its late Cenozoic tectonic and geomorphic evolution. The stratigraphic and structural observations indicate that the major bend in the fault was a releasing bend with significant Miocene sedimentation in the early–middle Miocene but became a restraining bend with abundant shortening structures developed after the late Miocene reversal of displacement. We also document exhumation of the shear zone from two low‐temperature thermochronologic transects. New apatite (U‐Th)/He(AHe) data and published thermochronologic results reveal two accelerated cooling episodes, backed by stratigraphic and geomorphic observations. The first rapid cooling phase occurred from ca. 27 to 17 Ma with removal of cover rocks and exhumation of the shear zone. The second accelerated cooling episode revealed by our AHe data commenced at 14–13 Ma, lasting 2–3 Myr. The Ailao Shan range may have risen to its modern elevation with high‐relief topography developing due to river incision. We interpret the onset of this rapid exhumation to reflect renewed plateau growth associated with lower crustal flow. Key Points: A releasing fault bend formed along the ASRR during left‐lateral shearing, changing to a restraining bend after right‐lateral reactivation The Ailao Shan Shear Zone experienced two phases of rapid exhumation in the Miocene The second cooling phase possibly reflects renewed plateau growth associated with lower crustal flow